Evaluation of Prevalence, Homology and Immunogenicity of Dispersin among Enteroaggregative Escherichia coli Isolates from Iran - Karam, Mohammad Reza Asadi (Iran Biomed J, 2017)
BACKGROUND: Diarrhea, caused by enteroaggregative Escherichia coli (EAEC), is an important infection leading toillness and death. Numerous virulent factors have been described in EAEC. However, their prevalence was highly variable among EAECs of distinct geographic locations. Studies have shown that dispersin (antiaggregation protein, aap) is one of the important and abundant virulent factors in EAEC. In this study, we aimed to determine the presence, conservation, and immunogenicity of aap gene in EAEC isolated from Iranian patients. METHODS: PCR amplification of aap gene in the EAEC isolates was performed, and the aap gene was cloned in pBAD-gIIIA vector. The sequence of aap gene was analyzed using the ExPASy and BLAST tools. The expression of aap gene was performed in E. coli Top10, and expression confirmation was carried out by SDS-PAGE and Western-blot techniques. Rabbits were immunized with purified dispersin protein emulsified with Freund’s adjuvant. Sera were collected and examined for antibody response. Finally, in vitro efficacy of dispersin and anti-dispersin was evaluated. RESULTS: The results of PCR showed the presence of aap gene in all of the EAEC isolates with significant homology. Finally, the significant difference between the levels of IgG response in dispersin-injected rabbits and control group was observed. CONCLUSION: Our results were in accordance with other studies that reported the presence of dispersin in the EAEC isolates with high conservation and immunogenicity. Hence, dispersin could be a promising candidate for any probable prevention against EAEC infections.